The Effectiveness Of Providing Different Natural Feed Types Of Swordtail (Xiphophorus Helleri) Broodstock On Crude Birth Rate (Cbr) - Susilawati Susilawati; Romi Susanti; Yudha Perdana Putra; Rizal Akbar Hutagalung; Muhammad Taufik (Universitas Tidar, 2021)
The most important factor in speeding up fish depends on the food given. The feed given was in the form of artificial feed (pellets) because of the practicality of its availability. However, commercially made feed was of course more expensive, and can pollute the air compared to natural feed which was easy and can be in the surrounding environment. For this reason, it was necessary to look for natural feed as an effective and efficient alternative feed to ripen the gonads of male and female swordtail. The research used a completely randomized design with 4 treatments and 3 repetitions and arranged randomly. Treatment by giving different natural food to the broodstock swordtail: treatment A (commercial pellets), B (Daphnia/Moina), C (blood worms) and D (mosquito larvae feed). Each broodstock treatment used was 27 females and 9 males (ratio 1: 3). The results of water quality measurements of all treatments with an average DO 4 mg/L, temperature 26 to 27oC, pH 7-8 and 30 mg/L hardness, thus showing the water quality during the research, the water condition was suitable for the maintenance of broodstock of swordtail, so that it supported growth. and breed of swordtail to produce tillers. The results showed that the highest average birth rate of swordtail broodstock produced in treatment D were 141 fish followed by treatment B 125 fish, then treatment C of 117 fish. and the lowest was in treatment A with a birth rate of 102 fish.